(3JbQjQ GdbhGYO hJMQjQ GdahGFOs - (3YHO GdQMef Hf CMeO Hf QLH GdMfHdj GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi egO bhGYO GdOjf HcJGHg GdeMce CeG HYO agPg bhGYO egeI hahGFO LeI bGYOI GdeGA GdLGQi gd gh cGdQGcO s
(3BNQgG (B:s
(3agh eecf CSde Ydi Ge hHfJ de jONd HgeG aEfg jKHJ fcGM GdHfJ Ohf GdCe hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHgG JdGejP GdeDda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B118s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs